THE COURSE OF CHRONIC VIRAL HEPATITIS B IN PREGNANT WOMEN - Tursunboyev Muxammadjon; Djuraeva Kamola Stanislavovna; Bekturdieva Shoira Sаtibаldievna (Web of Journals Publishing, 2024)
Viral hepatitis is one of the most significant public health problems worldwide, as chronic infection can lead to liver cirrhosis, hepatocellular carcinoma, and death [Yim SY, Kim JH. The epidemiology of hepatitis B virus infection in Korea.